Examining the Complexities of Parental Engagement at an Online Charter High School: A Narrative Analysis Approach - Borup, Jered; Walters, Shea; Call-Cummings, Meagan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
With the rapid growth of K-12 online learning opportunities, calls have come for more and better parental engagement to improve student engagement and reduce student attrition. In this article, we drew from a larger study to share rich narratives from three parents of students who required high levels of parental support for their online learning while enrolled at a charter cyber school. In the first narrative, a mother describes her experiences attempting to work with her son Ivan, who rejected her efforts and disobeyed rules while enrolled in the cyber school. The move from a brick-and-mortar school to the cyber school further strained their relationship and the mother was unprepared to manage Ivan’s learning. The second narrative focuses on how a mother attempted to support Matthew, who lacked self-regulation abilities. The mother who previously homeschooled Matthew, turned to the cyber school because she wanted “less on [her] shoulders” but underestimated the amount of support Matthew required and became frustrated at her lack of control over the pace and content of courses. The final narrative focuses on a mother who had two students enrolled in the cyber school. Each student exhibited different needs that required her to adapt the support strategies she used with Hannah, who procrastinated, and Karl, who lacked confidence. These narratives highlight some of the complexities parents navigate when engaging with their children’s online learning.